2014
DOI: 10.4236/pp.2014.51010
|View full text |Cite
|
Sign up to set email alerts
|

Nitridergic Modulation of the Antinociceptive Activity of Rosuvastatin in Mice

Abstract: Statins, 3-hydroxy-3 methylglutaryl coenzyme A (HMG-CoA) reductase enzyme inhibitors, are lipid-lowering drugs, often used in the treatment of cardiovascular diseases (hyperlipidemia, atherosclerosis). It has been shown that statins have antiinflammatory effects independent of their lipid-lowering effects and these anti-inflammatory effects inhibit the inflammation and pain process. This study evaluated the antinociceptive and anti-inflammatory effects of rosuvastatin using the acetic acid writhing, the formal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…Accordingly, the results of the present study show that rosuvastatin is a molecule capable of inhibiting pain and inflammation. Thus, the findings of this study are in agreement with previous results [2,3,[9][10][11][12][13]. This antinociceptive activity of statins deserves further study since it has been reported that these drugs have contradictory effects: they reduce neuropathic pain in animals but increase it in men.…”
Section: Discussionsupporting
confidence: 92%
“…Accordingly, the results of the present study show that rosuvastatin is a molecule capable of inhibiting pain and inflammation. Thus, the findings of this study are in agreement with previous results [2,3,[9][10][11][12][13]. This antinociceptive activity of statins deserves further study since it has been reported that these drugs have contradictory effects: they reduce neuropathic pain in animals but increase it in men.…”
Section: Discussionsupporting
confidence: 92%